Characterization of an Acetogenin-Carrying Nanosuspension and Its Effect on Bacteria of Interest in the Poultry Industry - Brandon A. López-Romero; Gabriela Aguilar-Hernández; Billy M. Hargis; María de Lourdes García-Magaña; Ulises M. López-García; Rosa I. Ortiz-Basurto; Adalberto Zamudio-Ojeda; Juan D. Latorre; Efigenia Montalvo-González (Microorganisms)
This work aimed to develop a nanosuspension (NSps) as an acetogenin (ACGs) carrier, using soy lecithin (SL) and hydroxypropyl-β-cyclodextrin (βCD) named NSps-βCDSL-ACGs. It was characterized by various spectroscopic techniques (DLS, FTIR, UV-vis diffuse reflectance). Moreover, the NSps morphology was observed by transmission electron microscopy (TEM). Also, the antibacterial activity of NSps-βCDSL-ACGs was evaluated against strains of interest in the poultry sector. NSps-βCDSL-ACGs presented nanometric size (207–239 nm), acceptable polydispersity index (PDI) values (0.13–0.17) and a high Z potential value (−47.17–50.36 mV), demonstrating high stability. The presence of ACGs in NSps-βCDSL-ACGs was confirmed by FTIR analysis. The nanoparticles had a spherical shape and exhibited high inhibition potential against Salmonella Enteritidis (88.18%), Streptococcus gallolyticus (88.01%), Salmonella Typhimurium (86.28%) and Salmonella Infantis (77.02%) strains up to 48 h, and a reduction of up to 3 log CFU/mL was achieved for S. Typhimurium. Therefore, NSps-βCDSL-ACGs is an attractive option for implementing ACGs administration in the poultry sector to reduce the use of antibiotics and minimize bacterial resistance.